3x- 11 +59 = 90
3x + 48 = 90
3x +48-48 =90-48
3x = 42
3x/3 = 42/3
x= 14
<MNQ = 3x -11
<MNQ = 3(14)-11
<MNQ = 42-11
<MNQ = 31
Answer:
The Answer is 3 - sqrt7
Step-by-step explanation:
2/3 + sqrt7 the starting equation
You multiply it by the conjugate which is 3 - sqrt7
= 2(3 - sqrt7) / (3 + sqrt7) (3 - sqrt7) the equation after you multiply by 3 - sqrt7
(3 + sqrt7) (3 - sqrt7) = 2
= 2(3 - sqrt7) / 2 the equation after you simplify (3 + sqrt7) (3 - sqrt7)
Divide out the 2's
= 3 - sqrt7/1 the equation after you divide out the 2's
= 3 - sqrt7 is THE ANSWER
Answer:
72 jelly beans
Step-by-step explanation:
138*0.52=71.76
round up
72
Answer:
87777777777777777777777777
Step-by-step explanation: